Pengaruh Keselamatan Dan Kesehatan Kerja, Lingkungan Kerja Non-Fisik Dan Kompensasi Terhadap Kinerja Karyawan PT PLN (Persero) UP3 Bekasi - Vida Rizqiyani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to determine the effect of occupational safety and health,non-physical work environment, and compensation on employee performance at PT PLN (Persero) UP3 Bekasi. Data collection was carried out by distributing questionnaires, research conducted on 50 respondents, a sample of several employees of PT PLN (Persero). Using the Likert Scale, respondents’ answers were processed with validity and reliability tests, classical assumption tests, multiple regression analysis, t tests, F tests, R2 tests. The result showed that all data tested were valid and reliable and found that partially occupational safety and health (X1) and non-physical work environment (X2) had a positive and significant influence on employee performance, but the variable X2 was greater in significance than the variable X1. And found that the compensation variable (X3) has a negative and insignificant influence on employee performance.